2022
DOI: 10.1037/pha0000422
|View full text |Cite
|
Sign up to set email alerts
|

Association of SAPAP3 allelic variants with symptom dimensions and pharmacological treatment response in obsessive–compulsive disorder.

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…While no studies of SPRED2 in patients with OCD have been published to date, a cautious affirmative answer can be offered in the case of SAPAP3 . A specific four-locus haplotype of SAPAP3 has been associated with an earlier age of onset in OCD, again pointing to a possible effect on neurodevelopment (Boardman et al, 2011 ); an allelic variant in a specific single nucleotide polymorphism ( rs 6662980) of SAPAP3 has been specifically associated with the Contamination/Washing dimension of OCD, as well as with a poor response to serotonin reuptake inhibitors (Naaz et al, 2020 ); and two single-nucleotide polymorphisms in SAPAP3 have been associated with symptom severity in early-onset OCD (Mas et al, 2016 ). In addition, a genome-wide association study has found that variations in SAPAP1 (also known as DLGAP1 ), coding for a protein related to SAPAP3 which is also involved in synaptic connectivity, were significantly associated with clinical OCD (Stewart et al, 2013 ).…”
Section: From Sapap3 To Spred2: Ocd and Neurodevelopment In Rodentsmentioning
confidence: 99%
“…While no studies of SPRED2 in patients with OCD have been published to date, a cautious affirmative answer can be offered in the case of SAPAP3 . A specific four-locus haplotype of SAPAP3 has been associated with an earlier age of onset in OCD, again pointing to a possible effect on neurodevelopment (Boardman et al, 2011 ); an allelic variant in a specific single nucleotide polymorphism ( rs 6662980) of SAPAP3 has been specifically associated with the Contamination/Washing dimension of OCD, as well as with a poor response to serotonin reuptake inhibitors (Naaz et al, 2020 ); and two single-nucleotide polymorphisms in SAPAP3 have been associated with symptom severity in early-onset OCD (Mas et al, 2016 ). In addition, a genome-wide association study has found that variations in SAPAP1 (also known as DLGAP1 ), coding for a protein related to SAPAP3 which is also involved in synaptic connectivity, were significantly associated with clinical OCD (Stewart et al, 2013 ).…”
Section: From Sapap3 To Spred2: Ocd and Neurodevelopment In Rodentsmentioning
confidence: 99%
“…Dysfunction in metabotropic glutamate receptor 5 (mGluR5) signaling and/or its interaction with postsynaptic density (PSD) scaffolding proteins is associated with repetitive motor dysfunction in numerous preclinical models for understanding psychiatric disorders [19,[37][38][39][40][41][42]. Of these, mutations in the striatal-enriched mGluR5 scaffold protein, disks large-associated protein 3 (SAPAP3), are associated with repetitive grooming and washing symptoms in OCSDs [43][44][45]. Genetic deletion of SAPAP3 in rodent results in striatal circuit abnormalities and increased mGluR5 function that promotes excessive grooming [13,[46][47][48][49][50][51][52], a complex sequential motor program that becomes excessively initiated and sustained despite negative consequences [53].…”
Section: Introductionmentioning
confidence: 99%